In tribute to Diderot: Milan Kundera, Jacques the Fatalist and their Master - Gawarecka, Anna (Poznańskie Studia Slawistyczne, 2018)
In his meta-literary and para-textual statements, Milan Kundera has been frequently turning to the issue of the enlightenment narrative experiments considered as the initial ones for the twentieth-century (post)modern creative strategies. Those experiments resulted from the striving for suppression of the over-prescription characterized the classicist rules, and they managed to direct attention to the literary genres which were undermined by the Enlightenment era that is in other words and above all, novel. In order to reveal this “modernity” of the eighteenth-century prose, the Czech writer in the work entitled Jacques and his master (1971) performed a “cultural translation” (variation) of the famous text by Diderot into the form of drama. Kundera was focused on the devices used by the French encyclopaedist which enabled him to expose the “evidence of trick” regarding the anti-illusion and fictitious character of literary representation of the world. He was, therefore, interested not so much in the philosophical and ideological background of Diderot’s tale dedicated to the romances of Jacques the Fatalist, but in the author’s freedom in his “play with the romance’s conventions” which even then was undergoing the process of fast schematisation.